Comparison of pain control between lignocaine and prilocaine spray versus oral analgesia in post-circumcision patients: a prospective randomized controlled trial in a tertiary care center - Nagabhairava, Manu K.; Kulkarni, Abhishek; Sangle, Ameya R.; Javali, Tarun; Reddy, Mani C.; P., Sandeep (International Journal of Research in Medical Sciences, 2024)
Background: Pain in the postoperative period is of particular concern. It is a major barrier in the uptake of circumcision. There are various systemic and local analgesics for the management of postoperative pain. However, data regarding efficacy is scarce. Therefore, the present pilot study was conducted to compare the efficacy of lidocaine and prilocaine spray with oral analgesics for the relief of pain. Methods: After obtaining ethics approval and written informed consent, 100 patients meeting the inclusion and exclusion criteria were included. After circumcision, patients were randomized into group A (Lidocaine and prilocaine spray) and group B (Oral analgesics). Pain was assessed by visual analogue scale (VAS) score and patient reported comfort levels were assessed in the postoperative period till 72 hours. Findings were noted and analysed. Results: Both the groups were similar in terms of demographic characteristics and baseline characteristics. The VAS score was significantly lower in group A and the patient-reported comfort level was significantly more in group A. Conclusions: We recommend that the lidocaine and prilocaine spray is better in relieving pain in the postoperative period following circumcision as compared to oral analgesics.